PENGARUH MASSAGE BABY TERHADAP PENINGKATAN BERAT BADAN BAYI USIA 3-6 BULAN DI KINARA BABY CARE BANTUL - Hermini, Hermini; Wulandari, Setyo Retno (Jurnal Kesehatan Samodra Ilmu (JKSI), 2021)
ABSTRACT Background : Massage therapy can have a very positive effect in the form of weight gain and increased breast milk consumption. Babies who are born normally aged 1-3 months if massaged for 15 minutes twice a week, after three weeks will experience a higher weight gain than babies who are not massaged. Massage is a tactile stimulation that has biochemical and physiological effects on various organs. body. Research methods : The method used was pre-experimental method. The research sample consisted of 15 babies aged 3-6 months in Kinara baby Care Bantul. The independent variable in this study is massage baby. The dependent variable measured was the baby's weight using the baby scales. The Wilcoxon test is used to analyze the effect of the independent variable and the dependent variable. Results and discussion : The results showed that there was a significant effect between infant massage and baby weight (p <0.05), p value = 0.001. This study showed that infant massage was effective in influencing changes, especially the increase in baby weight. There is an effect of baby massage on weight gain for infants aged 3-6 months at Kinara Baby Care